PENGARUH PENGGUNAAN UMPAN BALIK (FEEDBACK) TERHADAP HASIL BELAJAR SISWA DALAM MATA PELAJARAN FIQIH - Tomi Apra Santosa; Wulan Sari; Abi Suar; Jalwis Jalwis (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2020)
The purpose of the study was to find out the effect of user feedback on students' learning outcomes in fiqh subjects. This research includes quasi-experiments. The data is obtained through tests. Data analysis techniques Test t. Before implementing the hypothesis, a prerequisite test is carried out. The results showed that students without using the technique of feedback averaged 72.86 students with a standard deviation of 6,712 and variance of 45,055 and the value of students who used feedback techniques obtained from Postest grades with an average score of 82.50 with a standard deviation of 7,532 and variance of 56,751. The hypotheses obtained by T hitung = 3,838 > Ttabel = 2,145, the influence of the use of feedback on students' learning outcomes in the eyes of fiqh learning in grade XI IPA MAN 3 Kerinci. Learning with feedback techniques is suitable to be applied in public and religious schools.